Importance of Time Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
The lack of proper time management is causing stress and can ruin a career. Time management is a solution to the "not enough time" problem. Simply put, time management revolves around the tools, competencies, behaviors and attitude needed to work more efficiently every day. Everyone has to admit that wasting time is a favorite pastime for most senior members, and it is important for senior members to acquire time management knowledge in order to improve productivity. Time management is far more valuable than money. The importance of time is often forgotten and the idea to handle this. There are many senior members who often neglect time value. Any assistant registrar who is able to apply the art of time management has a better chance to be successful in life due to the ever-increasing competition on the job market today. This paper represents the importance of time management and Barriers to efficient time management.